The Therapeutic Potential of Ethnomedicinally Important Anatolian Thyme Species: A Phytochemical and Biological Assessment - Eroglu Ozkan, Esra; Ersoy, Ezgi; Yesil Canturk, Yeter; Mataraci Kara, Emel; Cinar, Ercan; Sahin, Hasan; Karahan, Selim; Karaca Sancaktepe, Kubra; Yilmaz, Mustafa Abdullah; Boga, Mehmet (Frontiers in Pharmacology, 2022)
Thyme has been used for various therapeutic purposes in almost every culture, which makes it one of the most riveting medicinal plants throughout history. From its beneficial effects on the respiratory tract or the gastrointestinal system, or to its unique skin-related activities, the investigation of the medicinal properties of thyme has always been an alluring topic for researchers with the ultimate goal of developing conventional medications from this traditional herb. With an incentive to contribute to this extensive thyme research, three Thymus species namely Thymus cariensis Hub-Mor. et Jalas (endemic), Thymus praceox subsp. grossheimi (Ronniger) Jalas, and Thymus pubescens Boiss. et Kotschy ex Celak from Turkey were deeply investigated within this study. The analysis of the phytochemical compounds of the extracts was conducted by LC-MS/MS, accordingly, 12 biologically important secondary metabolites (p-coumaric acid, caffeic acid, salicylic acid, quinic acid, fumaric acid, vanillin, malic acid, rutin, apigenin, naringenin, and nicotiflorin) were detected in all extracts. Their total phenolic and flavonoid contents were calculated (11.15±0.17 - 61.12±2.59 μg PEs/mg extract, 2.53±0.04 - 40.28±0.92 μg QEs/mg extract, respectively), and the antioxidant potential of the extracts was evaluated by DPPH and ABTS radical scavenging and CUPRAC activity methods, and the extracts were shown to possess significant antioxidant activity. Among them, Thymus cariensis stood out with IC50 values of 34.97±1.00 µg/mL and 9.98±0.04 µg/mL according to the DPPH and ABTS radical scavenging assays, respectively, and an A0.5 value of 5.80±0.02 µg/mL according to CUPRAC activity method. Their anticholinesterase, antityrosinase, and antiurease activities were also tested, Thymus cariensis (35.61±1.20%) and Thymus pubescens aerial part extract (33.49±1.39%) exhibited moderate antibutyrylcholinesterase activity at 200 µg/mL concentration. The results of the cell viability assay indicated that the extracts demonstrated moderate-to-low cytotoxicity on A498 human renal cell lines. Furthermore, all studied extracts exerted noteworthy antimicrobial activity, especially against Candida tropicalis (MIC values: 19.53 - 78.12 µg/mL). The presented data substantiates the use of thyme extracts as therapeutic agents in both ethnomedicine and conventional therapies.